2019
DOI: 10.11113/matematika.v35.n4.1266
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Domestic versus Global Prices Uncertainty on Sectoral Price Inflation in Malaysia

Abstract: Price stability is one of the main policy objectives that is targeted by policymakers in many countries. Price uncertainty occurs due to the changes in market structure and consumer preference and expectation, which may affect price stability. In this study, the researchers aimed to examine the effects of price uncertainty of consumer price disaggregation in Malaysian sectors. To be specific, the researchers were seeking to discover on how domestic and global commodity prices can affect sectoral Consumer Price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In economic literature, pharmaceutical products are acknowledged as an important item; consequently, inflation in their pricing increases the household budget (1). Numerous academics have shown that the inflation dynamics of industrialized nations have undergone significant modifications (2). Pharmaceutical businesses are experiencing increased pricing pressure which can be alluded to by the rise of the high inflation rate (3).…”
Section: Introductionmentioning
confidence: 99%
“…In economic literature, pharmaceutical products are acknowledged as an important item; consequently, inflation in their pricing increases the household budget (1). Numerous academics have shown that the inflation dynamics of industrialized nations have undergone significant modifications (2). Pharmaceutical businesses are experiencing increased pricing pressure which can be alluded to by the rise of the high inflation rate (3).…”
Section: Introductionmentioning
confidence: 99%